A Rare Metastasis of Prostate Cancer - İlkin Hamid-Zada; Bekir Demirtaş; Özgür Kazan; Özgür Efiloğlu; Asıf Yıldırım (Caucasian Medical Journal)
Prostate cancer is one of the most common cancers in men. Generally, prostate cancer metastases occur in lymph nodes and bones, but rare metastases, such as those in the kidneys, can be observed. There is no clear consensus regarding the diagnosis and treatment of renal metastases of prostate cancer. Our case report describes a 70-year-old male patient with a right renal mass detected on routine imaging due to elevated prostate-specific antigen levels 3 years after he was diagnosed with prostate cancer. For rare renal metastases, biopsy of the mass should be considered for diagnostic purposes.